1998
DOI: 10.1021/la9712101
|View full text |Cite
|
Sign up to set email alerts
|

Micropore Volume Filling. A Condensation Approximation Approach as a Foundation to the Dubinin−Astakhov Equation

Abstract: A volume filling of a single micropore and a two-dimensional (2D) condensation on its walls occur at the same critical pressure, and the local adsorption behavior may be modeled by the condensation approximation. This phenomenon underlies the approach to the micropore volume filling based on the condensation approximation (VFCA) and the Dubinin-Astakhov (DA) equation. The DA equation follows from the VFCA approach, being an approximate form to the general relationship. The physical meanings of the exponent, n,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Chen and Yang showed that n is really a structural parameter of carbon [25,38]. Dobruskin [39], considering the physical meaning of the parameters of DA equation, noticed that n does not depend on the pore dimensions and it is determined only by the standard deviation of micropore sizes, hence, it characterizes the surface heterogeneity. Similar conclusion was also provided by Jagiełło and Schwarz [36], Condon [40,41] as well as other authors.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Yang showed that n is really a structural parameter of carbon [25,38]. Dobruskin [39], considering the physical meaning of the parameters of DA equation, noticed that n does not depend on the pore dimensions and it is determined only by the standard deviation of micropore sizes, hence, it characterizes the surface heterogeneity. Similar conclusion was also provided by Jagiełło and Schwarz [36], Condon [40,41] as well as other authors.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose that adsorption phenomenon is pore filling by liquefaction, degree of the filling (u) is given as follows [47]:…”
Section: Correlation Methods By the Dubinin-astakhov Equationmentioning
confidence: 99%
“…Use of so-called non-symmetrical function in the condensation approximation (CA) and Langmuir isotherm (as the local isotherm) results in well-known DA isotherm in the form (Crittenden et al, 1999;Dobruskin, 1998;Podkos´cielny and La´szlo´, 2007;Yang and Xing, 2010;Yang et al, 2008Yang et al, , 2016:…”
Section: Adsorption Equilibriummentioning
confidence: 99%